2012
DOI: 10.1103/physrevlett.108.073002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of the Breit Interaction which Dominates the Angular Distribution of X-ray Emission in Dielectronic Recombination

Abstract: We report the experimentally determined angular distribution of the [1s2s(2)2p(1/2)](1)→[1s(2)2s(2)](0) transition in dielectronic recombination of Li-like Au. Recently, Fritzsche et al. [Phys. Rev. Lett. 103, 113001 (2009)] predicted that the Breit interaction plays a dominant role in the angular distribution of this transition. However, the predicted phenomenon has not yet been observed experimentally due to technical difficulties in conventional methods. To overcome the difficulties, we combine two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 27 publications
7
44
0
Order By: Relevance
“…The red curve in the upper plot corresponds to calculation of the total cross section within dipole approximation where only terms with j 0 = 1 are taken into account in the multipole expansion Eq. (17). The black curve in the upper plot corresponds to the full calculation (j 0 ≤ 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The red curve in the upper plot corresponds to calculation of the total cross section within dipole approximation where only terms with j 0 = 1 are taken into account in the multipole expansion Eq. (17). The black curve in the upper plot corresponds to the full calculation (j 0 ≤ 9).…”
Section: Resultsmentioning
confidence: 99%
“…The recent studies showed that the Breit interaction may give important and even dominant contribution to the cross section of the dielectronic recombination with few-electron highly charged ions [9,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there are few work about the linear polarization of tungsten X-ray emissions in ITER fusion plasmas. Since angle-resolved observables, such as linear polarization and angular distribution, are much more sensitive to various atomic effects and physical variables than the total (angle-averaged) decay rates of X-ray emissions, the angle-resolved studies of X-rays have been used to extract a variety of physical effects in the last few decades [30][31][32][33][34][35][36]. For those strong X-ray emissions from tungsten ions, they are hardly affected by the radiative damping caused by additional atomic excitation processes [27] and, thus, are relatively clean atomic radiations, which could be used to study the angle-resolved observables to reveal the population mechanism of excited levels [37,38] and perhaps to reflect plasma conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The measured intensity of the emitted radiation from these ions strongly depends on the angle of observation relative to the beam axis. There have been several studies reported in the literature for the polarization of radiation emitted from ions trapped in an EBIT (Henderson et al 1990;Beiersdorfer et al 1996;Taḱacs et al 1996;Gu et al 1999;Liang et al 2009a;Hu et al 2014b;Shah et al 2015). In the present study, we measured EUV spectra using CoBIT at 90…”
Section: Experiments and Data Analysismentioning
confidence: 95%